The UK National Registry of ABO and HLA Antibody Incompatible Renal Transplantation: Pretransplant Factors Associated With Outcome in 879 Transplants. Issue 7 (July 2017) - Pankhurst, Laura; Hudson, Alex; Mumford, Lisa; Willicombe, Michelle; Galliford, Jack; Shaw, Olivia; Thuraisingham, Raj; Puliatti, Carmelo; Talbot, David; Griffin, Sian; Torpey, Nicholas; Ball, Simon; et al.
Abstract : Background: ABO and HLA antibody incompatible (HLAi) renal transplants (AIT) now comprise around 10% of living donor kidney transplants. However, the relationship between pretransplant factors and medium-term outcomes are not fully understood, especially in relation to factors that may vary between centers. Methods: The comprehensive national registry of AIT in the United Kingdom was investigated to describe the donor, recipient and transplant characteristics of AIT. Kaplan-Meier analysis was used to compare survival of AIT to all other compatible kidney transplants performed in the United Kingdom. Cox proportional hazards regression modeling was used to determine which pretransplant factors were associated with transplant survival in HLAi and ABOi separately. The primary outcome was transplant survival, taking account of death and graft failure. Results: For 522 HLAi and 357 ABO incompatible (ABOi) transplants, 5-year transplant survival rates were 71% (95% confidence interval [CI], 66-75%) for HLAi and 83% (95% CI, 78-87%) for ABOi, compared with 88% (95% CI, 87-89%) for 7290 standard living donor transplants, and 78% (95% CI, 77-79%) for 15 322 standard deceased donor transplants ( P < 0.0001). Increased chance of transplant loss in HLAi was associated with increasing number of donor specific HLA antibodies, center performing the transplant, antibody level at the time of transplant, and an interaction between donor age and dialysis status. In ABOi, transplant loss was associated with no use of IVIg, cytomegalovirus seronegative recipient, 000 HLA donor-recipient mismatch; and increasing recipient age. Conclusions: Results of AIT were acceptable, certainly in the context of a choice between living donor AIT and an antibody compatible deceased donor transplant. Several factors were associated with increased chance of transplant loss, and these can lead to testable hypotheses for further improving therapy.